Theoretical investigation of low-valent uranium and transuranium complexes of a flexible small-cavity macrocycle: structural, formation reaction and redox properties. Issue 40 (18th July 2016) - Bao, Zhe; Zhao, Hong-Bo; Qu, Ning; Schreckenbach, Georg; Pan, Qing-Jiang
Abstract : Size matching of a flexible macrocycle with low-valent actinide(III/IV) ions as well as their bonding determines different coordination modes. Abstract : The flexible small-cavity macrocycle, trans -calix[2]benzene[2]pyrrolide (H2 L), has been found experimentally to complexate low-valent U III and U IV with binding pockets (BP ) of bis(arene) (Ar ) and bis(pyrrolide) (Pl ), respectively. This switchable coordination of the uranium center has been explored using relativistic density functional theory (DFT) in this work. Systematic calculations of [(BP -L)An m (η-H) n BH4− n )] z + (BP =Ar andPl ; An = U, Np and Pu; m = III and IV; n = 2 and 3; and z = 0 and 1), labeled asBP-An m -nH, were carried out. Energetics and geometrical/electronic-structure analyses reveal that the size matching between actinide ions and the binding pocket plays a significant role in determining the energetic ordering of isomers. The relatively large-size U III and Np III ions are selectively preferred by the large bis(arene) pocket, yielding the most stable isomer ofAr-An-2H ; simultaneously formed δ (An–Ar2 ) bonding helps stabilizing the system. In contrast, the small-size Pu III and An IV are held by the smaller bis(pyrrolide) to show the energetically favoredPl-An-3H isomer. This size argument is further supported by calculations on the related Th and Pa compounds. The formation reactions ofBP-An m -nH demonstrate an endothermic process when using the H2 L ligand reactant. Applying a more basic alkali ligand (A2 L; A = Li, Na and K) as the reactant significantly reduces the reaction energy and presents thermodynamic possibility to prepare the low-valent actinide complexes. This is in agreement with the experimental synthesis where K2 L was utilized. The redox potentials ( E 0 ) from tri- to tetravalent actinides were calculated while including both solvation and spin–orbit coupling effects. The highly reductive nature of the U III complex was manifested by the calculated E 0 of over 1.1 V.